Roland Barthes and La Préparation du Roman - Carneiro, Maria Clara da Silva Ramos (Lettres Françaises, 2009)
In his course La préparation du roman (“The Preparation of the Novel”), presented between 1978 and 1980, Roland Barthes discussed the form of the modern French novels taking into consideration the writings of great authors, as Proust, Mallarmé, Tolstoi, among others. In its introduction, the theoretician affi rmed that the course would be a “simulation” of a “novelist’s apprentice”. In the same period, several of his publications approached the same subject, his desire for a new type of writing, leading many writers to believe that he really intended to undertake the project of a greater Writing as he had described. Beyond the explicitation of the desire of “l’écriture” that we can observe in the Barthes of the last years of his life, the semiological criticism itself undertaken by him was accompanied by a wealth of “écriture” celebrated until today . Taking into consideration his studies as well as his publication of that period, I intend to discuss how Barthes’ writings are similar to what he describes as the “modern novel”.